Crosstalk of Microorganisms and Immune Responses in Autoimmune Neuroinflammation: A Focus on Regulatory T Cells - Schroeter, Christina B.; Huntemann, Niklas; Bock, Stefanie; Nelke, Christopher; Kremer, David; Pfeffer, Klaus; Meuth, Sven G.; Ruck, Tobias (Frontiers in Immunology, 2021)
Regulatory T cells (Tregs) are the major determinant of peripheral immune tolerance. Many Treg subsets have been described, however thymus-derived and peripherally induced Tregs remain the most important subpopulations. In multiple sclerosis, a prototypical autoimmune disorder of the central nervous system, Treg dysfunction is a pathogenic hallmark. In contrast, induction of Treg proliferation and enhancement of their function are central immune evasion mechanisms of infectious pathogens. In accordance, Treg expansion is compartmentalized to tissues with high viral replication and prolonged in chronic infections. In friend retrovirus infection, Treg expansion is mainly based on excessive interleukin-2 production by infected effector T cells. Moreover, pathogens seem also to enhance Treg functions as shown in human immunodeficiency virus infection, where Tregs express higher levels of effector molecules such as cytotoxic T-lymphocyte-associated protein 4, CD39 and CAMP and show increased suppressive capacity. Thus, insights into the molecular mechanisms by which intracellular pathogens alter Treg functions might aid to find new therapeutic approaches to target central nervous system autoimmunity. In this review, we summarize the current knowledge of the role of pathogens for Treg function in the context of autoimmune neuroinflammation. We discuss the mechanistic implications for future therapies and provide an outlook for new research directions.